(untitled) (American Journal of Islam and Society, 1987)
Introduction Adam Smith observed in his Wealth of Nations in 1776 that kings-or in my terminology the early bureaucratic leaders - existed already in “that rude state of society which precedes the extension of commerce and the improvement of manufactures” (Smith 1976: 907). Max Weber considered bureaucracy a necessary precondition for the development of society (Mieczkowski 1984: 105-06; Zinam 1984: 77-78) providing the element of functional organization and purpose. However, since power corrupts, it comes as no surprise that even the early bureaucratic leaders developed some dysfunctional traits, that corruption all too frequently became the prevalent mode of operation, and that the benign functional bureaucratic organizations, or ”borgs,” became in many cases transformed into “dysborgs,” or the dysfunctional bureaucratic organizations. An analysis of dysborgs and of some of their implications is offered in Mieczkowski and Zinam, Bureaucracy, Ideology, Technology: Quality of Life East and West (1984), and the terminology that is used in the present essay to interpret historical views, with their original concepts, will be from the Mieczkowski and Zinam book. Because the rudimentary bureaucratic organization developed early, some astute observers found already in remote times that bureaucracy is not always benign. It was, therefore, with great interest that I discovered one such observer who had been neglected by Western historians of economic thought, except for a footnote and a bare small-print mention in Joseph Schumpeter‘s History of Economic Analysis (1954: 136, 788), a footnote in Colin Clark’s Conditions of Economic Progress (1957: 6), and a footnote in Barry Gordon’s Economic Analysis Before Adam Smith (1957: 121). The writer in question was an Arab historian and philosopher, Ibn Khaldun (1332-1406), who covered many topics of interest to economists, and who in some respects was head of the founder of the science of economics, Adam Smith. Such occasional ...